SUFISME DALAM DODOLITDODOLITDODOLIBRET: CERPEN KARYA SENO GUMIRA AJIDARMA (Sufism in “Dodolitdodolitdodolibret” a Short Story by Seno Gumira Ajidarma) - Mulawati Mulawati (Balai Bahasa Sulawesi Selatan, 2014)
This article is a description about Sufism in Dodolitdodolitdodolibret, a short story by Seno Gumira Ajidarma.Basically, Sufism is a thought that drives human to get closed with spiritual attitude, to advise other people,hold promise to Allah swt, and to follow Prophet Muhammad in syari’ah. The article analyzes Sufism existing in the short story. Sufism is described by using descriptive qualitative method. After analyzing it, it could be concluded that sufism is shown by four activities. These activities are 1) the effort of keeping onleavingdesirewhich could be seen by the wish of characters to leave worldly pleasure, 2) searching of spiritual behaviorreflected by the characters’ effort to get closed with their God through praying, 3)giving advice for otherhuman which is shown by the main activity of Guru Kiplik, known as firm character to share his knowledgeof praying well, 4) the application of Rasulullah sunnah in life like praying as one of Rasulullah’s ways whenfacing challenge and suffering.